Acute effects of low dose of caffeine ingestion combined with conditioning activity on psychological and physical performances of male and female Taekwondo athletes - Ouergui, I.; Mahdi, N.; Delleli, S.; Messaoudi, H.; Chtourou, H.; Sahnoun, Z.; Bouassida, A.; Bouhlel, E.; Nobari, H.; Paolo Ardigó, L.; Franchini, E. (Nutrients, 2022)
This study investigated low-dose caffeine ingestion, conditioning activity (CA) effects on psycho-physical performances in young taekwondo athletes. In a randomized, double-blind, counterbalanced, crossover design, 20 athletes (10 males; 17.5 ± 0.7 yrs) performed taekwondo-specific agility test (TSAT), 10 s/multiple frequency speed of kick test (FSKT-10s/FSKT-mult) after ingesting 3 mg·kg-1 caffeine (CAF) or placebo (PL) 60 min before performing standard warm-up without (NoCA) or with CA (3 × 10 vertical jumps above 40 cm), resulting in four experimental (PL + NoCA, CAF + NoCA, PL + CA, and CAF + CA) and one control (warm-up session without CAF or CA) conditions. Mood/physical symptoms (MPSS), subjective vitality (SVS), and feeling (FS) scales were analyzed post-to-pre for all conditions. Ratings of perceived-exertion and perceived-recovery status were determined after tests. For TSAT, CAF + CA induced better performance compared with all conditions (p < 0.001). For FSKT-10s and FSKT-mult, CAF + CA induced better performance compared with all conditions (p < 0.001). For MPSS, FS, CAF + NoCA induced higher scores than PL + NoCA and PL + CA (p = 0.002, 0.009 for MPSS; p = 0.014, 0.03 for FS). For SVS, PL + CA elicited lower scores than PL + NoCA and CAF + NoCA (p = 0.01, 0.004). Sex comparisons resulted in better performances for males for TSAT (p = 0.008), FSKT-10s (p < 0.001), FSKT-mult (p < 0.01), MPSS (p = 0.02), SVS (p = 0.028), and FS (p = 0.020) scores. Caffeine and conditioning activity are two efficient performance-enhancing strategies, which could synergistically result in greater psycho-physical performances